Investigation of temperature effects on nanoscale water droplet separation from a nozzle plate and impingement onto a fixed solid plate. (October 2016) - Nguyen, Van Quang; Lin, Jau-Wen
Molecular dynamics simulation is used to study water molecular ejection through a 27.5-Å-diameter nozzle aperture under various system temperatures and pressing forces. In simulations, the effects of system temperature on the separation of water droplets from the nozzle plate surface are investigated. The results showed that the water nanojet did not separate from the nozzle plate surface at the system temperature of 310 K used to produce the nanoscale water droplets, regardless of the pressing forces. In addition, the impingement of nanoscale water droplets onto a fixed plate surface is also expressed. The contact angle, width of the spreading droplet, and average pressure of the droplets on the plate surface are discussed.